Effects of goal-framed and dynamic norm messages on national park campers' intentions to comply with wildlife attractant storage guidelines - Gorostiza, Jordan Matthew, author; Abrams, Katie M., advisor; Anderson, Ashley A., committee member; Niemiec, Rebecca, committee member (Colorado State University. Libraries, 2023)
Wildlife habituation and conditioning have posed persistent issues for managers of U.S. national parks and protected areas. The tendency for park campers to unintentionally feed wildlife by improperly storing known attractants contributes to these issues. There are park regulations requiring campers to properly store wildlife attractants that often go unfollowed. There is a noted management preference for addressing this noncompliance through communication. Previous research suggests that goal-framed and dynamic norm message frames may be effective at fostering behavioral antecedents and intentions to engage in pro-environmental behaviors such as proper attractant storage. This study examined if goal-framed and dynamic norm messages were effective at encouraging compliance. Results demonstrate no statistically significant impact on antecedents or intentions to store attractants from either goal-framed messages, dynamic norm messages, or goal-framed messages paired with dynamic norm messages. However, these statistically nonsignificant findings are aligned with a growing body of literature that have highlighted the complexities of accurately measuring the effects of goal-framed messages and the potential limited effectiveness of dynamic norm messages. Future research should focus on exploring these complexities in order to better understand how goal-framed and dynamic norm messages might be useful tools to park managers in mitigating the effects of negative human-wildlife interactions.
Keywords: human-wildlife interactions; national parks; regulatory focus; message framing; dynamic norms; natural resource management